REGISTER BAHASA GURU KREATOR KONTEN (GKK) DI MEDIA SOSIAL THREADS - hida, nova; Hari Sunaryo; Hari Windu Asrini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACTThe development of social media such as Threads has given rise to the phenomenon of content creator teachers (GKK), which creates a unique linguistic dynamic between the language of formal education and digital communication. This study aims to describe the form, function, and meaning of GKK language registers on the platform. With a descriptive qualitative approach, data were collected from the uploads of five GKK accounts (@fatkoer, @fikrisuhardi, @fiikriabdilah, @fakurly, @muchsinridlo) using listening, screen capture, and note-taking techniques. Data analysis followed the Miles and Huberman model, referring to word form theory (Ramlan, Kridalaksana), language function (Halliday), and meaning theory (Santoso, Keraf). The results show that GKK registers are in the form of single and complex words through affixation, reduplication, and abbreviation, and are mediated multimodally via hashtags and emojis. Language functions are dominated by representational and heuristic, followed by personal, instrumental, regulatory, and interactional, while imaginative functions are not found. On the meaning aspect, the register contains denotative and connotative meanings with meaning changes such as metaphor and peyoration. The conclusion of the study confirms that the GKK register is a form of hybridization that serves multiple functions: as an educational tool and a strategy to build authority, closeness, and professional identity in the digital space. This register represents teachers' linguistic adaptation that combines the brevity and appeal of digital communication without leaving the pedagogical essence.Keywords: register, language, content creator teacher, social media, threads, sociolinguistics